Mobile Application: Literary Reading Through Augmented Reality for Form 1 Students - ABD AZIZ, FADZILLAH BINTI (Journal of Computing Technologies and Creative Content, 2019)
Literature-based instruction is one of the approaches to teach students to read and it has been applied in English language class in secondary high school in Malaysia. There are many reading materials such as short stories, novel, and poems used as literature-based instruction approach. Literature-based instruction also helps in language growth such as English proficiency. However, using this approach is quite challenging for teachers as they need to come out with activities that require them to evaluate the content of the reading material and attract students that have no interest in reading. This will be time-consuming as the time is used to develop the activities. To improve the learning method and improve students performance in class, a mobile learning application will be developed which is an interactive AR literary reading application. This application is based on a short story taken from a Form 1 book which contains the literature component. It has simple animations and buttons were used to navigate thrrough the application. It aims to encourage the students to learn reading and improve their motivation in class using AR. Other activities were also included for better understanding of the reading materials. This application creates a new fun and joyful learning ambience in the classroom.